External and Internal Real Exchange Rates and the Dutch Disease in Africa: Evidence from a Panel of Nine Oil-Exporting Countries - (:unkn) unknown (My University, 2020)
Despite a large number of empirical studies on Dutch disease in developing countries and the evidence that oil revenues tend to appreciate the real exchange rate, there remains little discussion about the definition of real exchange rates. This article intends to fill this gap by using four different proxies of the real exchange rate, differentiating the internal and the external real exchange rates for agricultural and manufacturing sectors. Using Pooled-Mean-Group and Mean-Group estimates on a panel of nine African net oil-exporting countries, results show a clear appreciation of the RER generated by oil revenues except for the internal real exchange rate for manufacturing goods. This could imply that oil revenues more clearly affect agricultural compared to manufacturing competitiveness in these African countries.
Keywords: African Research